Challenges and Limitations among Foreign Medical Undergraduates interested in Research Study: A Cross-sectional Study - Nnaemeka Emmanuel Mgbedo; Karim Salimov; Daramola Oluwatosin; Eton Uduakabasi Noah Ededet; Nikita Vyas; Pragati Chhikara; Rupam Chaturvedi; Samuel Oluwatobi Odukoya; Olaniyan Ibraheem Olaniyi (International Journal of Medical Students)
BACKGROUND: Medical research holds immense significance in medicine as it propels progress, elevates patient care, and deepens our comprehension of diseases and therapies. We aimed to examine the barriers, and challenges that limit foreign medical undergraduates in conducting research studies.